Pathogenicity of the root-lesion nematode, pratylenchus zeae, on rice genotypes under different hydro-ecologies in Tanzania - Nzogela, Y.B.; Landschoot, S.; Kihupi, A.L.; Coyne, Danny L.; Gheysen, G. (Brill, 2020)
The root-lesion nematode, Pratylenchus zeae, is commonly found in upland rice fields. To measure the impact of the nematode on rice production, a screenhouse experiment was conducted using two farmer-adapted Oryza sativa cultivars, ‘Supa’ (‘SurinamV-880’) and ‘SARO-5’ (‘TXD 306’), under flooded, upland and drought water regimes imposed at 7 days post-inoculation of mixed-stage nematodes (200, 500, 1000, 3000 and 10 000 plant−1). Growth and yield parameters were recorded, and the experiment was terminated after 5 months. ‘Supa’ was shown to be resistant to P. zeae, while ‘SARO-5’ was susceptible. Pratylenchus zeae reduced the growth and yield of both cultivars, though more for ‘SARO-5’ than for ‘Supa’. Yield decreased with increasing final nematode densities. Pratylenchus zeae reproduction was highest at 200 and 500 inoculum levels and under upland water conditions. The yield of ‘SARO-5’ was greater than that of ‘Supa’ under flooded conditions and with no or 200 and 500 nematode inoculum levels, but with high P. zeae inoculum ‘Supa’ yield was better than ‘SARO-5’.